Morphological Disease Progression of Combined Pulmonary Fibrosis and Emphysema. Issue 2 (March 2015) - Matsuoka, Shin; Yamashiro, Tsuneo; Matsushita, Shoichiro; Fujikawa, Atsuko; Kotoku, Akiyuki; Yagihashi, Kunihiro; Kurihara, Yasuyuki; Nakajima, Yasuo
<x xml:space="preserve">Abstract</x> Objectives The purpose of this study was to evaluate the differences in 5-year morphological changes among the patients with combined pulmonary fibrosis and emphysema (CPFE), emphysema alone, and fibrosis alone using quantitative computed tomography evaluation. Methods This study involved 42 patients with CPFE, 45 patients with emphysema alone, and 35 patients with fibrosis alone who underwent computed tomography scans twice (initial and 5 years after the initial scan). The extent of emphysematous lesions was obtained by calculating the percentage of low attenuation area (%LAA) lower than −950 Hounsfield units. Fibrotic lesion was defined as a high attenuation area (HAA) using thresholds with pixels between 0 and −700 Hounsfield units, and the extent of fibrosis was obtained by calculating the mean percentage of HAA (%HAA). For the quantitative evaluation of the total area of emphysematous change and fibrosis, the percentage of destructed lung area (%DA) was obtained by summing %LAA and %HAA. The 5-year changes of %LAA, %HAA, and %DA were calculated. Differences were evaluated by 1-way analysis of variance, which was followed by the Tukey-Kramer test. Results The mean change of %LAA was significantly higher in CPFE (7.4% ± 3.8%) than in emphysema alone (P < 0.05). The mean change of %DA was significantly higher in CPFE (12.9% ± 5.8%) than in emphysema alone (4.9% ± 2.8%) and fibrosis alone (7.1% ± 5.7%). Conclusions Morphological disease progression in CPFE differed from that in emphysema alone or fibrosis alone. In particular, the increase in emphysematous low-attenuation lesions was significantly higher in CPFE.